(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
Increasing yield is one of the key focuses of the groundnut breeding program, but so is ensuring they are stable in diverse climatic conditions. Finding out the genotype (G) × environment (E) effect on the yield of groundnut through additive main effects and multiplicative interaction (AMMI) analysis. Five groundnut mutants underwent a multilocational study for two consecutive seasons at seven distinct locales. AMMI analysis was performed to determine the adaptation capabilities and the interaction between genotypes (G) and environment (E) of the genotypes. ANOVA revealed that the environment explained the greatest variation, 54.69%, while GEI explained 25.5% and genotype explained 19.81%. AMMI analysis revealed that GEN1 is the most adaptive genotype that can be grown throughout the environment, whereas GEN2 and GEN3 are unstable. The first two main interaction components explained 84.82% of the total GEI. The biplot of IPC1 and IPC2 revealed that GEN1 had a positive interaction with E1, E4, and E5. GEN4 and GEN5 revealed positive associations with E9. However, GEN2 and GEN3 contributed the major components of the GEI. Res. Agric. Livest. Fish. Vol. 11, No. 3, December 2024: 389-400